2011
DOI: 10.1111/j.1349-7006.2011.02111.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell receptor gene therapy targeting melanoma‐associated antigen‐A4 inhibits human tumor growth in non‐obese diabetic/SCID/γcnull mice

Abstract: Adoptive cell therapy with lymphocytes that have been genetically engineered to express tumor-reactive T-cell receptors (TCR) is a promising approach for cancer immunotherapy. We have been exploring the development of TCR gene therapy targeting cancer ⁄ testis antigens, including melanoma-associated antigen (MAGE) family antigens, that are ideal targets for adoptive T-cell therapy. The efficacy of TCR gene therapy targeting MAGE family antigens, however, has not yet been evaluated in vivo. Here, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 62 publications
2
18
0
1
Order By: Relevance
“…We previously described the importance of effector T-cell multifunctionality in the antitumor immune response [17][18][19], consistent with clinical observations reported by other groups [45,46]. The differences in the qualities of T-cell responses defined by different combinations of functions remain largely unknown.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We previously described the importance of effector T-cell multifunctionality in the antitumor immune response [17][18][19], consistent with clinical observations reported by other groups [45,46]. The differences in the qualities of T-cell responses defined by different combinations of functions remain largely unknown.…”
Section: Discussionsupporting
confidence: 70%
“…The mobilization of CD107a, a marker for the release of cytotoxic granules, was also elevated in cells stimulated with CH-296. We previously reported that the multifunctionality of effector CTLs, as assessed by the combination of these three measurements, is a critical determinant of the quality of the T-cell response [17][18][19]. The acquisition of multifunctionality by effector T cells is one mechanism by which these cells resist immunosuppression mediated by tumor progression in a model of adoptive transfer of tumor-specific T cells [17][18][19].…”
Section: Ch-296 Stimuli On Tcr Engagement Enhances Multifunctionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…MAGE, NY-ES0-1 and SAGE genes exhibit a similar expression pattern, and their immunogenicity as targets for cancer immunotherapy has been well-studied (12)(13)(14)(15)(16). In a recent study, we assessed the efficacy of immunotherapy for several types of cancer-targeting CTAs (17,18). As a first step towards the development of effective immunotherapy for RCC patients, it is crucial to evaluate the expression level of CTA in the targeted cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of efficacy, T cells expressing T cell receptors or chimeric antigen receptors specific for tumor or viral antigens can enhance anti-cancer or anti-infection effects. [6][7][8][9][10][11] And, as we will focus on in this study, T cells expressing suicide genes, which we prefer to refer to as cell-fate control genes, can be utilized to increase the safety of T cell therapy. In this approach, T cells expressing a cell-fate control gene can be adoptively transferred to mediate a therapeutic effect, with subsequent deletion of the gene-modified T cell population in vivo for prevention or treatment of T cell-mediated adverse effects.…”
Section: Introductionmentioning
confidence: 99%